2016
DOI: 10.1002/adom.201600122
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Hexagonal Diffraction Gratings as Optical Diffusers for In Situ Tunable Broadband Photon Management

Abstract: A stretchable transmissive hexagonal diffraction grating, which has the potential to act as an optical diffuser, is demonstrated. Leveraging the simplicity of the self‐assembly fabrication process, the photon manipulation capability of polystyrene nanosphere arrays, and elastomeric properties of polydimethylsiloxane, the proposed device is capable of reproducible in situ tuning of both diffraction efficiency and spectral range. While being able to achieve maximum diffraction efficiencies of about 80%, the devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…When subject to 50% strain, the normal transmittance of the film becomes as low as ≈15.5%. Other studies have reported that there is almost no normal transmittance change for a bare PDMS film under various tensile strains . After strain release, the normal transmittance spectra (average at 90%) almost reverts to that of the initial UVO‐treated PDMS film with almost no transmittance loss, because the film surface returns to the initial smooth state as demonstrated in Figure c.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…When subject to 50% strain, the normal transmittance of the film becomes as low as ≈15.5%. Other studies have reported that there is almost no normal transmittance change for a bare PDMS film under various tensile strains . After strain release, the normal transmittance spectra (average at 90%) almost reverts to that of the initial UVO‐treated PDMS film with almost no transmittance loss, because the film surface returns to the initial smooth state as demonstrated in Figure c.…”
Section: Resultsmentioning
confidence: 78%
“…Micro‐ and nanostructured soft surfaces offer a new strategy to dynamically tune optical properties by changing the surface topography without affecting the bulk properties . Recently, surface wrinkling has become a very cost‐effective, facile technology to reversibly control the surface topography, which inspired a wide range of applications such as thin‐film properties measurement, tunable adhesion and wettability, stretchable electronics, and optical materials/devices .…”
Section: Introductionmentioning
confidence: 99%
“…S11 ). To demonstrate the selective interaction between fingers and IR gratings, first we used the finite–difference time–domain approach ( 47 ) to simulate the θ in range of three different gratings ( Gt , Gi , and Gm ) in Fig. 4 A for first-order diffraction at θ d (φ = 270°, θ = 10°) ( SI Appendix , section 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, they cannot operate in car headlights, general lighting retrofit bulbsor or flashlights. [25] One of the most common applications of optical diffusers is the backlighting system of the LCDs. [24] Therefore, tailoring broadband directive emission profile for WOLEDs by wavefronts shaping technology is extremely appealing and scientifically curious for aforementioned specific applications.…”
mentioning
confidence: 99%
“…[25] One of the most common applications of optical diffusers is the backlighting system of the LCDs. [25] One of the most common applications of optical diffusers is the backlighting system of the LCDs.…”
mentioning
confidence: 99%